Smart Seeds for an Efficient and Sustainable Food System in the Philippines - Baruah, Sampriti; Mohanty, Samarendu (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The Philippines is one of the fastest-growing economies in Asia, with a gross domestic product (GDP) of USD 314 billion in 2017. A growing middle class and a large young population have been the main drivers of the Philippines’ economic dynamism (USDA, 2018). The country has grown consistently at more than 6% annually since 2012 and is expected to be a trillion-dollar economy by 2030. Agriculture continues to remain a key economic pillar, contributing approximately 12% of the country’s GDP and employing about 32% of the economically active population.